Thyroid autoimmunity and adverse pregnancy outcomes: A multiple center retrospective study - Xu, Yun; Chen, Hui; Ren, Meng; Gao, Yu; Sun, Kan; Wu, Hongshi; Ding, Rui; Wang, Junhui; Li, Zheqing; Liu, Dan; Wang, Zilian; Yan, Li (Frontiers in Endocrinology, 2023)
Background: The relationship between thyroid autoimmunity (TAI) and adverse pregnancy outcomes is disputable, and their dose-dependent association have not been fully clarified. Objective: To investigate the association and dose-dependent effect of TAI with multiple maternal and fetal-neonatal complications. Methods: This study is a multi-center retrospective cohort study based on singleton pregnancies of three medical college hospitals from July 2013 to October 2021. The evolution of thyroid function parameters in TAI and not TAI women were described, throughout pregnancy. The prevalences of maternal and fetal-neonatal complications were compared between the TAI and control group. Logistic regression was performed to study the risk effects and dose-dependent effects of thyroid autoantibodies on pregnancy complications, with adjustment of maternal age, BMI, gravidity, TSH concentrations, FT4 concentrations and history of infertility. Results: A total of 27408 participants were included in final analysis, with 5342 (19.49%) in the TAI group and 22066 (80.51%) in control group. TSH concentrations was higher in TAI women in baseline and remain higher before the third trimester. Positive thyroid autoantibodies were independently associated with higher risk of pregnancy-induced hypertension (OR: 1.215, 95%CI: 1.026-1.439), gestational diabetes mellitus (OR: 1.088, 95%CI: 1.001-1.183), and neonatal admission to NICU (OR: 1.084, 95%CI: 1.004-1.171). Quantitative analysis showed that increasing TPOAb concentration was correlated with higher probability of pregnancy-induced hypertension, and increasing TGAb concentration was positively correlated with pregnancy-induced hypertension, small for gestational age and NICU admission. Both TPOAb and TGAb concentration were negatively associated with neonatal birthweight. Conclusion: Thyroid autoimmunity is independently associated with pregnancy-induced hypertension, gestational diabetes mellitus, neonatal lower birthweight and admission to NICU. Dose-dependent association were found between TPOAb and pregnancy-induced hypertension, and between TGAb and pregnancy-induced hypertension, small for gestational age and NICU admission.